Caracterização das ações realizadas no âmbito de subprojetos Pibid/Capes de educação física no Rio Grande do Sul - Costa, Thais Machado (2015)
The research reported here aimed to establish possible links of the actions taken in subprojects PIBID / CAPES curricular area of physical education (PE) in the state of Rio Grande do Sul (RS) with the developed in the Superior Teaching Institutions (HEI) and the Schools and Basic Education (BSE). In that sense, we seek to answer the following research problem: What major features characterize the actions carried out in subprojects PIBID / CAPES curricular area of Physical Education developed in the state of Rio Grande do Sul? We focus our study in Higher Education Institutions (HEI) are developing subprojects PIBID / CAPES this curriculum area in RS. We used as sources of information: (1) subjects, 10 and 47 BCA Bank; (2) Documents (10 full texts of these subprojects analyzed by own script). Regarding the analysis of the actions developed by Subprojects PIBID / CAPES curricular area of EF, we can say that: the organization of subprojects PIBID / CAPES respects the norms present in Ordinance No. 096, but differ in the number of scholarship holders involved, the level of activity and the number of shares set out in the full text of subprojects. Regarding development of the actions carried out in subprojects was possible to see the disparity in the distribution of the work hours of the IDB, as it was also possible to see that the texts of the subprojects are not detailed the specific actions of the stock market, but based on the speech of the same is can assign own shares to them. Among the relations between the actions carried out in subprojects and the situation of PE in schools involved found that the meaning attributed to EF in school requires attention by pointing out relevant ills as the EF as a wildcard element, the replacement of lessons per festivities, difficulties teachers in justifying their practice and the gap between theoretical frameworks of the area and the actions undertaken in schools. The relations established by the IDB between the actions carried out in subprojects PIBID / CAPES and the activities developed in the undergraduate programs allow us to observe the gap of knowledge transmitted in the disciplines of the school situations undergraduate courses. These actions demonstrate the existence of peculiarities in the organization of subprojects.